Seasonality of rainfall erosivity and soil loss extremes and variability in Douro vineyard plots - Figueiredo, Tomás de (2022)
Seasonality and frequency of erosive rainfalls largely affects runoff and soil loss and should drive timing of soil conservation practices and farm operations, an important issue for reducing on-site and off-site erosion impacts in vineyards. This study aims at exploring seasonality and frequency of rainfall erosivity and their relation to the erosional response of vineyard plots located in the Douro Wine Region. Data used in the study are the 10-year records from 5 plots at Quinta de Santa Bárbara, Pinhão (rainfall, runoff, soil loss, vine phenology and tillage operations). EI30 (reference rainfall erosivity index) was computed for different rainfall intensity and height thresholds. IDF curves were derived for durations from 5 min to 24h. Frequency analysis of rainfall height, intensity and erosivity were performed on annual and seasonal basis.Rainfall erosivity is the main factor explaining plots erosional response. From all computed indexes, the best performing was EI30m, calculated with all rains (no threshold), relating at event level in a power function with soil loss (r=0.713). EI30m (796 MJ ha-1 mm h-1 annual average) correlated very well with the original EI30, calculated for events above defined rainfall height threshold (r=0.997). Seasonality affected IDF curves parameters, higher intensity being found in summer than in winter rains for durations shorter than 3 hours. Out of 167, 3 extreme erosion events accounted for ¾ of the total soil loss in 10 years and resulted from rainfalls with return periods from 20 to 100 years. Annual average soil loss has a typical negative exponential relationship with plots vegetation cover. However, plot cover provided by plantation schemes and practices in Douro Wine Region may result insufficient to limit to tolerable rates soil losses triggered by high erosivity rainfalls, using actual vegetation cover management practices alone.